Cross-cultural adaptation and validation of Dysphagia Handicap Index in Bangladesh - Mehrin Sultana; Md. Muid Hossain Reshad; Md. Shohidul Islam Mridha (Journal of Patient-Reported Outcomes)
Abstract The Dysphagia Handicap Index (DHI) is commonly utilized for evaluating how dysphagia impacts the quality of life (QoL) of patients across physical, functional, and emotional dimensions. The primary aim of the research was to linguistically validate and culturally adapt the DHI to the Bangla version. A cross-sectional study design was chosen, with Beaton’s protocol as the guiding framework for validating and adapting the DHI. It has followed a systematic process of forward translation, participation in expert discussions, and subsequent back translation to obtain a reviewed version. The Bangla version, DHI-Ban, was administered purposefully to 50 dysphagia patients in the Clinical Speech and Language Therapy (SLT) Department of the Centre for the Rehabilitation of the Paralyzed (CRP) and was also administered to 50 healthy individuals for comparison. Of the fifty, eighteen dysphagia subjects were assigned again after two weeks for the retest. The DHI-Ban demonstrated strong internal consistency (Cronbach’s α = 0.89) and good test-retest reproducibility (ICC = 0.86). The Spearman test confirmed significant construct validity (p < 0.01), and the Wilcoxon test identified significant differences (p < 0.001) between patients and healthy individuals. Feedback from participants was also taken into account for acceptance and clarity. In conclusion, the adapted DHI-Ban has emerged to be a reliable patient-reported tool for assessing dysphagia in Bangla-speaking individuals. Incorporating the Bangla language framework facilitates its comprehension and effectiveness, further solidifying its reliability.